2018
DOI: 10.1177/0958928718804930
|View full text |Cite
|
Sign up to set email alerts
|

Asset-based welfare: Is housing equity release a viable option for pensioners in Slovenia

Abstract: The transformations in the welfare state regimes that have occurred globally, over the last three decades or so, have seriously affected the capacity of states to sustain the previous levels of social care and protection. These changes, already being manifested, inter alia, in trends in declining earnings of pensioners have inspired some researchers in this field to explore alternative ways of mitigating their impact on the well-being of the elderly during the retirement period. One of the theories that has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…In the nutshell, there is a lack of financial consumers' interest for introducing the RM loans in Croatia for the time being. Obtained results are in line with those for other CEE countries, likewise Slovenia (Sendi et al, 2019), Slovak Republic (Husáková et al, 2018) or Poland (Zbrojewski, 2013).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the nutshell, there is a lack of financial consumers' interest for introducing the RM loans in Croatia for the time being. Obtained results are in line with those for other CEE countries, likewise Slovenia (Sendi et al, 2019), Slovak Republic (Husáková et al, 2018) or Poland (Zbrojewski, 2013).…”
Section: Introductionsupporting
confidence: 88%
“…The research of 930 Slovenian financial consumers that were aged 50 years and over by Sendi et al (2019) reveals strong rejection of the RM product, as only 1.6% of the total number of respondents declared that they would accept a loan model of RM. The logistic regression results show that the younger respondents and those with higher level of education were more inclined towards the equity release.…”
Section: Factors Influencing the Rm Introduction And Acceptancementioning
confidence: 99%
“…The Nigerian market is especially difficult given the macroeconomic volatility that makes policies to become unstable and therefore unreliable in the long term. Sendi et al (2019) also conducted a study on the role of mortgage in housing finance in Slovenia. The study whose main aim was to explore the role mortgage lending play in housing finance in Slovenia revealed that the National Housing Fund (NHF), which is a Low-income earners in Bauchi LGA, Nigeria public agency, dominate majority of the Slovenian housing finance market, because of weak primary and non-existing secondary mortgage market.…”
Section: Performance Of Financing Institutionsmentioning
confidence: 99%
“…The post-communist countries of central and eastern Europe (among them Slovenia) are characterised by very high levels of homeownership [17]. As stated by Sendi et al [76], homeownership can be an important financial asset under the condition of increasing care costs and withdrawal of the welfare state. The results of this study showed that all groups except one (the first group) would have the use of this financial asset while enacting their potential option of moving.…”
Section: Discussionmentioning
confidence: 99%